A Timely Administration of Antenatal Steroids Is Highly Protective Against Intraventricular Hemorrhage: An Observational Multicenter Cohort Study of Very Low Birth Weight Infants - Fortmann, Ingmar; Mertens, Luisa; Boeckel, Hannah; Grüttner, Berthold; Humberg, Alexander; Astiz, Mariana; Roll, Claudia; Rickleffs, Isabell; Rody, Achim; Härtel, Christoph; Herting, Egbert; Göpel, Wolfgang; et al. (Frontiers in Pediatrics, 2022)
Aim: To evaluate the influence of the timing of antenatal steroids (ANS) on neonatal outcome of very low birth weight infants (VLBWI) born below 30 weeks of gestation in the German Neonatal Network. Methods: The German Neonatal Network is a large population-based cohort study enrolling VLBWI since 2009. We included 672 neonates into our analysis, who were born between January 1st, 2009, and December 31st, 2019, in 10 selected centers. Infants were divided into four subgroups based on the interval between the first steroid administration and preterm birth: (I) Two doses of betamethasone, ANS-birth interval: >24 hours to 7 days, n=187, (II) only one dose of betamethasone, ANS-birth interval 0-24h, n=70, (III) two doses of betamethasone, ANS-birth interval >7 days, n=177 and (IV) no antenatal steroids, n=238 . Descriptive statistics and logistic regression analyses were performed for main neonatal outcome parameters. Group IV (no ANS) was used as a reference. Results: An ANS-birth interval of 24h to 7d after the first dose was associated with a reduced risk for intraventricular hemorrhage (OR 0.17; 95% CI 0.09-0.31, p<0.001) and mechanical ventilation (OR 0.37; 95% CI 0.23-0.61, p<0.001). Whereas the group of infants that only received a single dose of steroids reflected a subgroup at high risk for adverse neonatal outcomes, an ANS-birth interval of >7 days was still associated with a lower risk for intraventricular hemorrhage (OR 0.43; 95% CI 0.25-0.72, p=0.002) and the need for mechanical ventilation (OR 0.43; 95% CI 0.27-0.71, p=0.001). Conclusion: Our observational data indicate that an ANS-birth interval of 24h to 7d is strongly associated with a reduced risk for intraventricular hemorrhage in VLBWI. Further research is needed to improve the prediction of preterm birth in order to achieve a timely administration of antenatal steroids that may improve neonatal outcomes such as intraventricular hemorrhage.